miRNA and cholesterol homeostasis - Jeon, Tae-Il (Biochim Biophys Acta, 2016)
MicroRNAs (miRNAs) have recently emerged as a novel class of epigenetic regulators of gene expression. They are systemically involved in the control of lipid metabolism through a complex interactive mechanism that involves gene regulatory networks. Hence, they can contribute to defective lipid metabolism and metabolic diseases. Here, we review recent advances in the roles of lipid-sensing transcription factors in regulating miRNA gene networks, as well as miRNA expression and function in the regulation of cholesterol metabolism.